From Service Quality to Public Trust: Procedural Justice in Frontline Police Services - Habib Awuliya Nani; Alexande Badjuka; Alfiah Agussalim; Yanti Anet; Rahmatia Pakaya; Yakob Noho Nani (Journal of Creative Power and Ambition (JCPA), 2026)
In the context of contemporary public administration, service quality is no longer understood solely as a matter of administrative efficiency or procedural compliance, but as a relational process that shapes citizens' experiences of the state itself. The purpose of this study is to examine how procedural justice shapes citizens' trust in frontline police services at the Gorontalo Regional Police Service Center (SPKT), Indonesia. This study employed a qualitative mechanism-based case study method, with data collected through in-depth interviews, observation, and document analysis. The findings suggest that trust is shaped less by the speed of service than by fairness of treatment, clarity of procedures, consistency of interactions, and visible complaint handling. This study identifies an administrative legitimacy gap and argues that police service quality should be understood as justice-based service legitimacy, not merely administrative performance.